Yoga for Patients with Early Breast Cancer and its Impact on Quality of Life – a Randomized Controlled Trial - Siedentopf, F.; Utz-Billing, I.; Gairing, S.; Schoenegg, W.; Kentenich, H.; Kollak, I. (Geburtshilfe und Frauenheilkunde, 2013)
The aim of this prospective, randomized, controlled trial was to investigate the impact of yoga on newly diagnosed patients with early breast cancer in the immediate postoperative phase. 93 women newly diagnosed with early breast cancer were randomized into an intervention group (IG) and a control group (waiting group, WG). The IG started yoga immediately after the operation. The WG started yoga 5 weeks after surgery. Both groups attended yoga classes twice weekly for 5 weeks. Quality of life (QoL) was evaluated using the EORTC QLQ-C30 and EORTC QLQ-BR23 questionnaires before the intervention, immediately after the operation and after 3 months. After 3 months the patients were asked whether yoga improved their physical activity and whether they wished to continue with yoga. The overall QoL (p = 0.002) and the functional status (p = 0.005) increased significantly in the IG, while physical symptoms decreased over time in both groups. 86 % of patients in the IG and only 59 % of patients in the WG (p = 0.04) confirmed a positive change in their physical activity through yoga. More women in the IG intended to continue with yoga (p = 0.03). Early initiation of yoga as a supportive treatment in cancer had a positive impact on QoL. Teaching yoga allowed patients to practice yoga by themselves, enhanced the patientsʼ QoL and was found to improve physical activity.
Keywords: breast cancer; yoga; oncological care; quality of life